A crítica ao SUS no jornal Folha de São Paulo - Silva, Gabriela Martins (2010)
This paper aims to study the construction of the criticism of the SUS (Brazilian National Health System) in the newspaper Folha de São Paulo during the year of 2008, considering the meanings attributed to the system, to its directors and to its users. With this analysis we aim to collaborate with the discussions around the importance of SUS disclosure to put in effect its principles and Social Control. To do so, the analysis of 667 news articles selected by researching the papers files on line was conducted. Critical discourse analysis and contributions of the social constructionist perspective, methodological lenses which invite us to explain the constructed character of social realities, considering the effects of different forms of construction for the various actors and social institutions were used. Thus, we studied the process of news production, trying to understand what meanings have been constructed or privileged from the use of different linguistic resources, analyzing it as a textual practice, and the influence of journalistic style in the construction of these meanings, analyzing it as a discursive practice. With this process, we delimited the construction of SUS ineffectiveness, the (in)competence of the government and (in)determination of the user insertion. The ineffectiveness of SUS was built upon some discursive strategies that call for: (1) The appointment of SUS, in terms of its problematic aspects and little on its successfulness, (2) Health care system in crisis, characterized by the repetition of the word crisis and generalization of problematic areas to the role System, (3) The eternal memory of the bad, delimited by the use of "despite" and "but" in order to bring about problematic aspects of the System, and (4) The irony of SUS, marked by the use of irony when talking about the services. In the construction of the (in) competence of government, we found: (1) The demoralization of the government, signaling the intent to conceal data upon its owns problem, (2) Others who do better with private, international and philanthropic at the expense of public and national, (3) The voice of the experts attesting to the incompetence of government, with the illegitimacy of the official voice, (4) Personalization of the government, as the actions of the government are explained by the motivations, wishes and affections of the people who govern, (5) The focus on time, naturalizing the lateness of health interventions. In regards to (in) determination of the insertion of the user in the System, we delimited three discursive strategies: (1) Depoliticization of the user, marked by the insertion of the user from the use of different services in non committing manners, (2) Limited politicization, characterized by a political participation restricted to enclosed spaces or consenting to some social sectors, and (3) Judicialization, marked by the requirement of individual rights through legal proceedings. Thus, erasing of the possibility of acting through boards of health and /or health conferences was found. These directions were produced from the search for "scoops", featured in our study by (1) seasonality in the publication of news, (2) the use of "bombastic" headlines (3) simplicity, with the aim of providing understanding of the news by more people, and (4) by using visibility features, such as data accumulated, comparisons and concrete metaphors. All these features and meanings provide a limited and negative view of the SUS, based on mistrust and inability to improve the system. Moreover, since the construction of government (in)competence and the (in)determinacy of insertion of the user, we believe that social control disclosure does not occur as a form of promoting participation in the SUS, which hides the history and the democratic process of its construction.